Pengaruh Psychological Well-Being terhadap Work Engagement melalui Mediasi Lingkungan Kerja (Studi pada Prajurit) - Mohammad Ikhwanur Rokhim; Suryani Hardjo; Hasanuddin Hasanuddin (Mahesa Research Center, 2023)
The purpose of this study was to identify the effect of psychological well-being on work engagement through mediation of the working environment (studies on soldiers). The research methodology that used in this paper is Structural Equation Modeling (SEM), which uses Structural Equation Modeling (SEM) analysis software with Smart PLS. In the first hypothesis it was found that the effect of psychological well-being of working environment on soldiers with a t-count is about 33.253 > 1.96 and a p-value is 0.000 <0.05. The second hypothesis found that there was an effect of the working environment on work engagement in soldiers, with a t-count is 1.571 <1.96, and a p-value is 0.117 > 0.05. The third hypothesis, found that there is an effect of psychological well-being on work engagement in soldiers, with a t-count of 6.341 > 1.96, and a p-value of 0.000 <0.05. The fourth hypothesis found that there is a mediating role of the working environment in the influence of psychological well-being on work engagement in soldiers, with a direct effect value of PWB on WE is about 0.517 (51.7%) greater than the indirect effect of PWB on WE through LK is 0.110 (11). .0%) is significant at 0.05 (5%). Judging from the existing problems, it is hoped that input and assistance for personnel to develop, conduct work motivation, communicative, or other training that can increase work engagement.